Analysis of laparoscopic cholecystectomy after endoscopic retrograde cholangiopancreatography for choledocholithiasis-a prospective study - Mir, Shakeel Ahmad; Bali, Rajandeep Singh; Ahmad, Aijaz; Khan, Alam Manzoor (International Surgery Journal, 2022)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecystectomy (LC) remains the cornerstone of treatment worldwide for coexisting CBD and gall bladder calculi. The interval between ERCP and LC is disputed. In our study, LC is performed at or more than 6 weeks after ERCP keeping in view by allowing the gall bladder to recover from the acute inflammatory changes if operated upon earlier. Methods: We conducted a prospective observational study in the postgraduate department of general surgery government medical college Srinagar J and K India over a period of 2 years. The 25 patients above age of 18 years and with cholecysto-choledocholithiasis who underwent ERCP and LC at or more than 6 weeks were included. Results: In our study the mean age was 45.3 years. Male: female ratio was 1:3.2. the distribution of patients as per Nassar grading scale 1 (4%) patient had grade I,12 (48%) patients had grade II, 5 (20%) patients had grade III and 7 (28%) patients had grade IV. In patients with grade I, the mean duration of surgery was 36.0 minutes, in grade II the duration of surgery ranged from 34-60 minutes with mean duration of surgery of 43.4 min (SD±8.9), in grade III duration of surgery ranged from 42-68 minutes with mean duration of surgery of 55.2 min (SD±10.06) and in grade IV duration of surgery ranged from 68-116 minutes with mean duration of surgery of 91.3 min (SD±17.66). We observed a definite relationship between the intraoperative Nassar grading scale and the post ERCP interval, 1 patient of grade I scale operated at 12 weeks post ERCP. 12 patients were between the post ERCP interval of 8-12 weeks (mean 10.1 weeks) and they had grade II. In grade III we had 5 patients with post ERCP interval of 7-11 weeks (mean 9.2 weeks). In grade IV we had 7 patients with post ERCP interval of 6-10 weeks (mean 7.9 weeks). p=0.008. Conclusions: Interval LC after ERCP is safe but challenging, longer the interval time between ERCP and LC lesser the chances of encountering intra-operative complications. We recommend LC more than 6 weeks after ERCP is safe.